2016
DOI: 10.3389/fncom.2016.00126
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Coupling between Cortical Oscillations and Muscle Activity during Isotonic Wrist Flexion

Abstract: Coupling between cortical oscillations and muscle activity facilitates neuronal communication during motor control. The linear part of this coupling, known as corticomuscular coherence, has received substantial attention, even though neuronal communication underlying motor control has been demonstrated to be highly nonlinear. A full assessment of corticomuscular coupling, including the nonlinear part, is essential to understand the neuronal communication within the sensorimotor system. In this study, we applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 69 publications
10
37
0
Order By: Relevance
“…Recently, we proposed a frequency domain approach namely cross‐spectral coherence (CSC) to investigate the nonlinear corticomuscular interaction (Yang et al ., ). CSC is a generalised coherence framework for quantifying nonlinear coupling between signals across different frequency bands as well as the linear coupling within the same frequency band (Yang et al ., ).…”
Section: Assessing the Nonlinear Corticomuscular Interactionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, we proposed a frequency domain approach namely cross‐spectral coherence (CSC) to investigate the nonlinear corticomuscular interaction (Yang et al ., ). CSC is a generalised coherence framework for quantifying nonlinear coupling between signals across different frequency bands as well as the linear coupling within the same frequency band (Yang et al ., ).…”
Section: Assessing the Nonlinear Corticomuscular Interactionmentioning
confidence: 97%
“…Using CSC and independent component analysis, we assessed both linear and nonlinear interaction between muscle activity and multiple brain sources in healthy participants during an isotonic wrist flexion task (Yang et al ., ). In consistent with previous studies, we found beta‐band peak in the linear corticomuscular interaction for both motor and sensory‐related cortices, that is primary sensorimotor areas (S1‐M1), premotor area (PMA), supplementary motor area (SMA) and posterior parietal cortex (PPC).…”
Section: Assessing the Nonlinear Corticomuscular Interactionmentioning
confidence: 97%
“…There are several important considerations in its current formulation (H4: relationship between motor unit actions and force). [36][37][38][39][40][41][42] The question of why force is related to the rectified sEMG, and not to sEMG, apparently has to see with the way in which sEMG is recorded, using pairs of electrodes symmetrically placed at both sides of the neuromotor innervation zone on the muscle, as suggested by the experts. 37,39 The force exerted by a muscle is a consequence of the neuromotor stimulation of the muscular fibers by impulse-like action potentials, 43 which accumulate on the muscular cell membranes as a de facto integration of the positive peaks of individual actions, therefore the muscular force appearing responds to the rectified integral of sEMG recordings (r m (t)).…”
Section: Neuromechanic Articulation Modelmentioning
confidence: 99%
“…1D) was then obtained with parameters 'nvoice' (scale resolution of the wavelet), 'J1' (number of scales) and 'wavenumber' (Morlet mother wavelet parameter) set, respectively, to 0.125, 871 and 7 to yield accurate identification of oscillatory activity from 0.13 Hz to 114.39 Hz in 1.07 Hz step. EMG signals were not rectified to properly model EMG time series as centered Gaussian processes (Bigot et al, 2011;Charissou et al, 2016) and not to lose important information contained in the EMG signal spectrum (Neto & Christou, 2010;McClelland et al, 2012;Yang et al, 2016). The wavelet cross-spectrum ( Fig.…”
Section: Corticomuscular Coherencementioning
confidence: 99%
“…where S EEG, EEG (x, u) is the wavelet cross-spectrum between EMG and EEG signals (Eqn 2), and S EMG (x, u) and S EEG (x, u) are the wavelet auto-spectrum of each EMG and EEG signal (Eqns 3 and 4). The magnitude of the CMC was calculated from 0 to 1 bounded corticomuscular values as the volume under the time-frequency map of magnitude-squared coherence only where the wavelet crossspectrum between the EEG and EMG signals was detected as significant (Charissou et al, 2016;Yoshida et al, 2017). Over the [+3 + 6] s period of interest, the magnitude of the CMC was computed in two frequency bands of interest: [8-13] Hz (CMC 8-13 ) (Christou et al, 2007) and [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Hz (CMC 13-31 ) .…”
Section: Corticomuscular Coherencementioning
confidence: 99%